The Changes of Behaviors and Cognitive Functions by Cognitive Behavioural Therapy in the Drug Abusers - Herni Susanti (Jurnal Ners, 2010)
Introduction: This study was aimed to find out the effect of CBT on the behaviors i.e. depressive, agressive and antisocial behaviors as well as cognitive functions of patients who were treated in rehabilitation unit at a drug addiction hospital (Rumah Sakit Ketergantungan Obat) in Jakarta.Method: The research design was Quasi experimental pre-post test without control group by providing intervention: CBT for 6 sessions (10–12 times intervention). The population was all patients in the rehabilitation unit with a nursing diagnosis: low self esteem and/or inffective coping strategies. There were 23 participants who involved in this investigation. The data was analized by using dependent and independent sample t, and anova tests.Result: The results showed that p value for depressive behaviours, agressive behaviurs, antisocial behaviors, and cognitive functions were 0.914; 0.001; 0.039; 0.003 respectively. The outcomes indicated that there was significant impact of CBT on agressive behaviors, antisocial behaviors, and cognitive functions (α = 0.05, p value < 0.05), but not on depressive behaviors (α = 0.05, p value > 0.05).Discussion: It is argued that depressive symptoms might not be apparent for the users in rehabilitative phase. The findings also showed that there was significant relation between antisocial behaviors and the length of drug usage. This affirms exsiting concepts in that long drug usage brings about serious damage in the users' behaviors and cognitive functions. It is recommended, therefore, to include CBT as an important intervention for clients with drug abuse problems who are cared in rehabilitation center.The Changes of Behaviors and Cognitive Functions by Cognitive Behavioural Therapy in the Drug Abusers